OH and COOH functionalized single walled carbon nanotubes-reinforced alumina ceramic nanocomposites - Zaman, Ali Can; Ustundag, Cem B.; Kaya, Figen; Kaya, Cengiz (ELSEVIER SCI LTD, 2012)
Alumina ceramics reinforced with 1 wt.% single-walled carbon nanotube (SWCNT) were fabricated via spark plasma sintering (SPS) of composite powders containing carboxyl (COOH) or hydroxyl (OH) group functionalized single-walled carbon nanotubes. The samples were SPS'ed at 1600 degrees C under 50 MPa pressure for holding time of 5 min and at a heating rate of 4 degrees C/s. The effects of CNT addition having different surface functional groups on microstructure, conductivity, density and hardness were reported. It was shown that nanotube addition decreased the grain sizeof alumina from 3.17 mu m to 2.11 mu m for COOH-SWCNT reinforcement and to 2.28 mu m for COOH-SWCNT reinforcement. The hardness values of the composites are similar for all samples but there is 4.5 and 7.5 times increase in electrical conductivity with respect to monolithic alumina for COOH-SWCNT and OH-SWCNT, respectively. It was also shown by TEM and FEG SEM observations that transgranular fracture behaviour of alumina was changed to mostly intergranular fracture mode by the addition of both types of CNTs which may be due to location of CNTs along the grain boundaries. A significant grain size reduction in alumina is considered toresult fromthe suppressing effect of CNTs during sintering. (C) 2011 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Al2O3; Carbon nanotube; Spark plasma sintering; Functional groups; MECHANICAL-PROPERTIES; COMPOSITES; DISPERSION; Materials Science